Spatial diversity of the skin bacteriome - Pérez-Losada, Marcos; Crandall, Keith A. (Frontiers in Microbiology, 2023)
The bacterial communities of the human skin impact its physiology and homeostasis, hence elucidating the composition and structure of the healthy skin bacteriome is paramount to understand how bacterial imbalance (i.e., dysbiosis) may lead to disease.To obtain an integrated view of the spatial diversity of the skin bacteriome, we surveyed from 2019 to 2023 five skin regions (belly button, behind ears, between toes, calves and forearms) with different physiological characteristics (dry, moist and sebaceous) in 129 healthy adults (579 samplesafter data cleaning). Estimating bacterial diversity through 16S rRNA metataxonomics, we identified significant (P<0.0001) differences in the bacterial relative abundance of the four most abundant phyla and 11 genera, alphaand beta-diversity indices and predicted functional profiles (36 to 400 metabolic pathways) across skin regions and microenvironments. No significant differences, however, were observed across genders, ages, and ethnicities. As previously suggested, dry skin regions (forearms and calves) were more even, richer, and functionally distinct than sebaceous (behind ears) and moist (belly button and between toes) regions. Within skin regions, bacterial alpha-and beta-diversity also varied significantly for some of the years compared, suggesting that skin bacterial stability may be region and subject dependent. Our results, hence, confirm that the skin bacteriome varies systematically across skin regions and microenvironments and provides new insights into the internal and external factors driving bacterial diversity.